Hmmm .-.
f(x) = 5x + 2x - x!
f(2)
f(x) = 5x + 2x - x!
f(2)
Penjelasan dengan langkah-langkah:
f(x) = 5x + 2x - x!
f(2) =
_________________________
f(x) = 5x + 2x - x!
f(2) = 5(2) + 2(2) - 2!
f(2) = ( 5 × 2 ) + ( 2 × 2 ) - ( 2 × 1 )
f(2) = 10 + 4 - 2
f(2) = 14 - 2
f(2) = 12
[tex]\boxed{\pink{\mathscr{Lzynnn}}}[/tex]
Penjelasan dengan langkah-langkah:
f(x) = 5x + 2x - x!
f(2) = ... ?
f(x) = 5x + 2x - x!
f(2) = 5(2) + 2(2) - (2×1)
f(2) = (5×2) + (2×2) - (2×1)
f(2) = 10 + 4 - 2
f(2) = 14 - 2
f(2) = 12
[answer.2.content]